2009
DOI: 10.1007/s10637-009-9360-3
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyltin(IV) complexes containing arylazobenzoate ligands: chemistry, in vitro cytotoxic effects on human tumor cell lines and mode of interaction with some enzymes

Abstract: Dibutyltin(IV) complexes of composition Bu₂Sn(LH)₂, where LH is a carboxylate residue derived from 2-[(E)-(5-tert-butyl-2-hydroxyphenyl)diazenyl]benzoate (L¹H) with water molecule (1), 4-[(E)-(5-tert-butyl-2-hydroxyphenyl)diazenyl]benzoate (L²H) (2) and 4-[(E)-(4-hydroxy-5-methylphenyl)diazenyl]benzoate (L³H) (3), were synthesized and characterized by spectroscopic (¹H, ¹³C and ¹¹⁹Sn NMR, IR, ¹¹⁹Sn Mössbauer) techniques. A full characterization was accomplished from the crystal structure of complex 1. The mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…Further, these ligands and their analogues have been explored for their coordination behaviour towards organotin(IV) in order to find possible candidates in this class of organotin(IV) complexes which might act as anticancer drugs owing to their remarkable cytotoxic activity that has been exhibited in some cases across a panel of cell lines [3][4][5]. As a result of promising cytotoxic activity [6,7], the mechanistic role of these organotin(IV) compounds was investigated, to see influence of the azo group nitrogen atoms, by docking studies with some of the key enzymes such as ribonucleotide reductase, thymidylate synthase, thymidylate phosphorylase and topoisomerase II that take part in the synthesis of raw materials for DNA and its replication [3][4][5]. The docking studies indicated that the azo group nitrogen atoms and formyl, carbonyl and ester oxygen atoms in the ligand moiety play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Further, these ligands and their analogues have been explored for their coordination behaviour towards organotin(IV) in order to find possible candidates in this class of organotin(IV) complexes which might act as anticancer drugs owing to their remarkable cytotoxic activity that has been exhibited in some cases across a panel of cell lines [3][4][5]. As a result of promising cytotoxic activity [6,7], the mechanistic role of these organotin(IV) compounds was investigated, to see influence of the azo group nitrogen atoms, by docking studies with some of the key enzymes such as ribonucleotide reductase, thymidylate synthase, thymidylate phosphorylase and topoisomerase II that take part in the synthesis of raw materials for DNA and its replication [3][4][5]. The docking studies indicated that the azo group nitrogen atoms and formyl, carbonyl and ester oxygen atoms in the ligand moiety play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…We recently investigated the cytotoxic potential of triphenyltin (IV) 2-[(E)-2-(aryl)-1-diazenyl]benzoates and dibutylbis{2-[(E)-2-(aryl)-1-diazenyl]benzoato}tin(IV) and found to exhibit high activity when tested in vitro against human tumor cell lines [17,18]. Among these, the triphenyltin(IV) compounds were found to be better performers than dibutyltin(IV) compounds.…”
mentioning
confidence: 99%
“…Among these, the triphenyltin(IV) compounds were found to be better performers than dibutyltin(IV) compounds. Further, the molecular docking studies of these compounds indicated that the azo group nitrogen atoms and formyl, carbonyl, ester and hydroxyl oxygen atoms in the ligand moiety exhibit hydrogen bonding interactions with the active site of the amino acids of various enzymes, such as ribonucleotide reductase, thymidylate synthase and thymidylate phosphorylase [17,18]. The high activity was attributed to the presence of an azo group in the organotin(IV) complexes molecules [17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in organotin compounds in general and organotin carboxylates in particular continues to grow because of their biological activity and potential antineoplastic, antituberculosis agents [21,22]. Among those compounds dibutyltin derivatives have displayed both higher activity and lower toxicity [23]. Organotin complexes derived from carboxylic acids are among the most extensively studied class of compounds owing to their rich structural chemistry.…”
Section: Introductionmentioning
confidence: 99%